Conditional genome engineering reveals canonical and divergent roles for the Hus1 component of the 9–1–1 complex in the maintenance of the plastic genome of Leishmania. Issue 22 (31st October 2018) - Damasceno, Jeziel D; Obonaga, Ricardo; Silva, Gabriel L A; Reis-Cunha, João L; Duncan, Samuel M; Bartholomeu, Daniella C; Mottram, Jeremy C; McCulloch, Richard; Tosi, Luiz R O
Abstract: Leishmania species are protozoan parasites whose remarkably plastic genome limits the establishment of effective genetic manipulation and leishmaniasis treatment. The strategies used by Leishmania to maintain its genome while allowing variability are not fully understood. Here, we used DiCre-mediated conditional gene deletion to show that HUS1, a component of the 9–1–1 (RAD9-RAD1-HUS1) complex, is essential and is required for a G2/M checkpoint. By analyzing genome-wide instability in HUS1 ablated cells, HUS1 is shown to have a conserved role, by which it preserves genome stability and also a divergent role, by which it promotes genome variability. These roles of HUS1 are related to distinct patterns of formation and resolution of single-stranded DNA and γH2A, throughout the cell cycle. Our findings suggest that Leishmania 9–1–1 subunits have evolved to co-opt canonical genomic maintenance and genomic variation functions. Hence, this study reveals a pivotal function of HUS1 in balancing genome stability and transmission in Leishmania . These findings may be relevant to understanding the evolution of genome maintenance and plasticity in other pathogens and eukaryotes.